1993
DOI: 10.1002/j.1460-2075.1993.tb06142.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the nucleosomes at the replication fork.

Abstract: The fate of parental nucleosomes during chromatin replication was studied in vitro using in vitro assembled chromatin containing the whole SV40 genome as well as salt‐treated and native SV40 minichromosomes. In vitro assembled minichromosomes were able to replicate efficiently in vitro, when the DNA was preincubated with T‐antigen, a cytosolic S100 extract and three deoxynucleoside triphosphates prior to chromatin assembly, indicating that the origin has to be free of nucleosomes for replication initiation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 49 publications
(100 reference statements)
9
111
0
Order By: Relevance
“…In contrast, our data of the first transfer distance peaked at 500-700 bp, and do not support histone dissociation and diffusion. Previous studies also provide evidence indicating that during replication, parental histones are not released into solution 7,8,22 , arguing against a diffusion-based mechanism. Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, our data of the first transfer distance peaked at 500-700 bp, and do not support histone dissociation and diffusion. Previous studies also provide evidence indicating that during replication, parental histones are not released into solution 7,8,22 , arguing against a diffusion-based mechanism. Fig.…”
Section: Resultsmentioning
confidence: 97%
“…During DNA replication, dsDNA available for nucleosome transfer is located behind the replication fork on the nascent daughter duplexes, which are poised to accept parental nucleosomes from ahead of the replication fork 22,34,35 . We hypothesize that if nucleosome transfer is dictated by DNA loop formation, transfer should take place on the upstream dsDNA, in a similar manner as demonstrated for the downstream dsDNA.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, data from some other groups suggest the parental octameric structures are disrupted during the passage of replication fork (Sogo et al, 1986;Fotedar and Roberts, 1989), and some H2A/H2B dimers dissociate from replicating DNA (Jackson, 1987(Jackson, , 1990. Finally, using an improved in vitro replication method, Gruss et al clarified the debate and provided further insights (Gruss et al, 1993). The authors concluded that, a subnucleosomal particle, probably the (H3/H4) 2 tetramer is the transfer unit, which, then assembled with two H2A/H2B dimers to form an intact nucleosome.…”
Section: Early Investigations On Rc Nucleosome Assembly and Their Conmentioning
confidence: 99%
“…The authors concluded that, a subnucleosomal particle, probably the (H3/H4) 2 tetramer is the transfer unit, which, then assembled with two H2A/H2B dimers to form an intact nucleosome. In addition, 5-10 folds of competitor DNA during replication traps histones transferred to daughter strands, suggests that the histones may only loosely associated with replicating DNA (Gruss et al, 1993). However, a few open questions remain, such as what are the chaperon factors that assist the disassembly/reassembly process of the parent nucleosomes and how they coordinate with chaperons facilitate the deposition of newly synthesized histones.…”
Section: Early Investigations On Rc Nucleosome Assembly and Their Conmentioning
confidence: 99%
See 1 more Smart Citation